PENURUNAN DROP TEGANGAN PENYULANG 20 KV DENGAN METODE PECAH BEBAN - Ramadhan, Roby; Lesmana, Dicky; Tharo, Zuraidah (Politeknik Harapan Bersama Tegal, 2024)
The electricity distribution system is essentially a process of delivering electricity from power generation systems to electricity consumers through a 500/150/70 kV Transmission Network to electricity consumers at 20 kV or 220/400 V. The electricity distribution process begins from the output of the 20 kV substation to the consumers. The distribution of electricity when it exits the substation will pass through feeders. Feeders are the pathways for distributing 20 kV of electricity to distribution substations. Feeders are one of the most crucial parts of the electricity distribution process. As the customer load increases and the length of the lines on each feeder, it can cause an increase in current load and voltage drop. According to SPLN 72: 1987 regulations, in medium voltage networks, the spindle configuration voltage drop limit is 2% of the operating voltage. Therefore, feeders experiencing voltage drops must implement feeder splitting methods to reduce voltage drops at the end of the line. By implementing load splitting on the Curriculum and Report feeders by adding a new feeder, namely the Academy feeder, the voltage drop at the end of the lines does not exceed SPLN standards. The Curriculum feeder is at 2.7%, the Report feeder is at 2.06%, and the Academy feeder is at 1.4%.